Risk Measurement of Islamic Banking Financing Portfolio in Indonesia Based on Value at Risk Variance–Covariance - Germansah, Germansah; Jiblathar, Panji; Mubarak, Fadhlul (Benefit: Journal of Bussiness, Economics, and Finance, 2026)
This research is motivated by the importance of risk measurement of Islamic banking financing portfolios that have different contract characteristics. The purpose of this study is to analyze the risk of the financing portfolio based on the type of contract using the Value at Risk approach based on variance-covariance. The method used is a quantitative approach with data on the time sequence of Islamic banking financing in Indonesia, which is analyzed through the measurement of returns, volatility, and correlations between financings. The findings show that portfolio risk is heterogeneous, with project-based financing showing the highest level of risk, while asset-based financing shows a greater level of stability. Furthermore, it can be seen that interactive relationships can be leveraged to facilitate risk diversification. In conclusion, Value at Risk-based risk measurement is able to provide a more comprehensive picture of potential portfolio losses and support more effective risk management.